Adaptations of Bacillus shacheensis HNA-14 required for long-term survival under osmotic challenge: a multi-omics perspective. Issue 48 (2nd August 2018) - Long, Xiufeng; Tian, Jiewei; Liao, Xuepin; Tian, Yongqiang
Abstract : The osmoprotection mechanism of halophilic bacteria Bacillus shacheensis HNA-14 under different nutrient conditions with high salt concentration for long-term survival. Abstract : Genomic sequence, transcriptomic, metabolomic and fatty acid analyses of strain HNA-14 were performed to understand the mechanism of salt tolerance for long-term survival. The results indicated that strain HNA-14 has different osmotic resistance mechanisms for long-term survival and short-term salt stress. The cells mainly synthesized compatible solutes to resist osmotic pressure when cultured under nutrient deficient conditions, while they can slow down the synthesis rate and uptake from the environment when cultured under a nutritionally rich environment. Also, the amounts of branched and unsaturated fatty acids in the cell membrane are maintained to a high degree (>50%) to maintain the fluidity of the cell membrane; when the cells are cultured in a high osmotic environment for long-term survival, they may increase the content of branched fatty acids and phosphoric fatty acids to increase the fluidity of the cell membrane to resist the high osmotic pressure.